Wavelike interfacial design and mechanical behaviour of joint between Si-SiC coated carbon/carbon composites and Li2O-Al2O3-SiO2 glass ceramics. Issue 5 (1st April 2018) - Zhao, Fengling; Fu, Qiangang; Wang, Lu; He, Song
Abstract: A new insight of the oxidation phenomenon utilisation of Si-based ceramics was proposed to strengthen the joining of carbon/carbon (C/C) composites and Li2 O-Al2 O3 -SiO2 (LAS) glass ceramics. A Si-based ceramic coated C/C substrate with a porous surface was achieved by the in-situ reaction method coupled with the high-temperature pre-oxidation. The porous structure would contribute to the formation of a wavelike interface through hot-pressing sintering of the C/C-LAS joints. The prepared wavelike interface could significantly increase the joining area. Moreover, according to the results of the simulation, the thermal stress distribution around the designed interface was relieved. Therefore, the apparent shear strength of the C/C-LAS joints with the designed interface was strengthened to 32.46 ± 1.35 MPa, 51% higher than those without interfacial design.